2019
DOI: 10.4274/tjps.galenos.2018.58815
|View full text |Cite
|
Sign up to set email alerts
|

Considering the Effect of <i>Rosa damascena</i> Mill. Essential Oil on Oxidative Stress and <i>COX-2</i> Gene Expression in the Liver of Septic Rats

Abstract: Sepsis, tüm dünyada yüksek ölüm oranına sahip klinik bir hastalıktır. Oksidatif stres sepsiste ortaya çıkan önemli bir olgu olarak kabul edilir. Rosa damascena Mill., farmakolojik aktiviteleri yüksek olan eski bir bitkidir. Gereç ve Yöntemler:Standart bir model olarak çekal ligasyon ve ponksiyon (CLP), sıçanlarda sepsis oluşturmak için kullanılmıştır. Erkek yetişkin sıçanlar rastgele 5 gruba ayrılmıştır. R. damascena uçucu yağları (50 ve 100 mg/kg) 14 gün boyunca oral yolla verilmiş ve 15. günde CLP uygulanmış… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Studies showed that active peptides with antioxidative and immunomodulatory properties produced during the fermentation process (Korhonen and Pihlanto 2003;Sachindra and Bhaskar 2008). Moreover, our results are in conjunction with other studies, which showed that CLP could alter the level of antioxidant enzyme in liver and lung tissues, while pretreatment with Rosa damascena and Mentha longifolia essential oils could modulate the level of MPO, GSH, and LP (Dadkhah et al 2018(Dadkhah et al , 2019.…”
Section: The Effects Of Fsbm On Lung Biochemical Enzyme In Septic Ratssupporting
confidence: 86%
“…Studies showed that active peptides with antioxidative and immunomodulatory properties produced during the fermentation process (Korhonen and Pihlanto 2003;Sachindra and Bhaskar 2008). Moreover, our results are in conjunction with other studies, which showed that CLP could alter the level of antioxidant enzyme in liver and lung tissues, while pretreatment with Rosa damascena and Mentha longifolia essential oils could modulate the level of MPO, GSH, and LP (Dadkhah et al 2018(Dadkhah et al , 2019.…”
Section: The Effects Of Fsbm On Lung Biochemical Enzyme In Septic Ratssupporting
confidence: 86%
“…radical scavenging effects of phenolic compounds and flavonoids presented in the oils. Our current study indicated the in vivo anti-inflammatory activities of Rosa damascena essential oils may be associated with their antioxidant compounds namely citranellol, trans geraniol and phenylethyl alcohol as the main constituents of the essential oils which proved antioxidant activities by DPPH and β-carotene/linoleic acid bleaching assays 8. Previous study also revealed that the essential oil of rosemary containing antioxidant compounds has a strong antioxidant and hepatoprotective activities by modulating the malondialdehyde (MDA) and GSH levels and also catalase (CAT), peroxidase (Px), glutathione peroxidase (GPx), and glutathione reductase (GR) activities.…”
mentioning
confidence: 60%
“…significantly affect oxidative stress/antioxidant parameters and detoxifying enzymes as well as COX-2 gene expression. 8 There is also an evidence indicating the hepatoprotective activity of deuterium depleted water against acetaminophen. 7 Following this, the present study was designed to consider, for the first time, the therapeutic efficacy of DDWs and DDWs plus RD against liver injury induced by CLP in septic rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations